Kesantunan Verbal dan Non-Verbal dalam Etika Bisnis Budaya Jepang kepada Para Staff PT PRPP Jawa Tengah untuk Meningkatkan Hospitality dan Servis Excellence - Rina Supriatnaningsih; Lisda Nurjaleka; Silvia Nurhayati; Anggraeni; Dwi Puspitosari; Yoyok Nugroho (Varia Humanika, 2024)
Verbal and non-verbal politeness in Japanese cultural business ethics given to PT PRPP Central Java staff as part of tourism business actors can improve service with hospitality in accordance with the transformation of PT PRPP Central Java into a Tourism Holding Company. This excellent service can be realized with verbal and non-verbal services from a blend of Indonesian and Japanese politeness. As a result of the training from verbal practice in Japanese culture, the training staff consisted of 23 participants consisting of operational managers, HRD managers, cashier supervisors, marketing supervisors, marketing staff, general affairs supervisors, Public Relations, security coordinators, security members, electrical mechanic coordinators, freelancers tickets, and internship participants at PT PRPP, based on the results of a questionnaire via google form after being given training, it can be concluded that participants can learn to introduce themselves by using the ending desu or masu in the use of greeting sentences 'good morning' by saying ohayou gozaimasu, not pronounced with ohayou. When introducing themselves, the staff can say sentences, such as ….. desu or …. to moushimasu ‘I ……’. Non-verbal polite service, staff can do ojigi or 'bow' to show courtesy to others while exchanging business cards or meishi as part of the Japanese culture of business ethics. In addition, the staff can practice writing their own names in Japanese characters using katakana letters as evidenced by uploading the name card files that all participants have made